FBXW8 suppresses PDCoV proliferation via the NPD52-dependent autophagic degradation of a viral nucleocapsid protein - Ji, Likai; Zhou, Liying; Wang, Ying; Yang, Shixing; Liu, Yuwei; Wang, Xiaochun; Shen, Quan; Zhou, Chenglin; Xu, Juan; Zhang, Wen (Frontiers in Immunology, 2024)
Porcine deltacoronavirus (PDCoV), a newly discovered intestinal coronavirus, has rapidly spread among pigs worldwide and has shown the potential for cross-species infection. However, the interaction mechanism between PDCoV and the host’s antiviral response is still poorly understood. In this study, an E3 ubiquitin ligase FBXW8 was explored on PDCoV proliferation. Our findings demonstrate that PDCoV infection increases the expression of FBXW8 through p65-mediated activation of its promoter. We also discovered that FBXW8 suppresses PDCoV replication by directly targeting and inducing the degradation of the PDCoV-encoded nucleocapsid (N) protein. Interestingly, FBXW8 catalyzes the K48-linked polyubiquitination of the PDCoV N protein at a unique lysine-rich region (KR). Furthermore, we observed that the FBXW8-ubiquitinated PDCoV N protein interacts with NDP52, a cargo receptor, leading to autophagic degradation instead of proteasomal degradation. In summary, these findings reveal FBXW8 as a novel host antiviral factor involved in PDCoV infection. It mediates the NDP52-dependent autophagic degradation of the PDCoV N protein. These results provide new insights and a potential target for host defenses against PDCoV.